Предмет: Математика,
автор: нурай205
2,4 * (6 - 3x) + 4,3 = 1,7 - 5,2x
Ответы
Автор ответа:
0
2,4( 6 - 3х ) + 4,3 = 1,7 - 5,2х
14,4 - 7,2х + 4,3 = 1,7 - 5,2х
- 7,2х + 5,2х = 1,7 - 18,7
- 2х = - 17
х = 8,5
14,4 - 7,2х + 4,3 = 1,7 - 5,2х
- 7,2х + 5,2х = 1,7 - 18,7
- 2х = - 17
х = 8,5
Автор ответа:
0
2,4*(6-3х)+4,3=1,7-5,2х
14,4-7,2х+4,3=1,7-5,2х
-7,2х+5,2х=-14,4-4,3+1,7
-2х=-17
х=17:2
х=8,5
--------------------------------------------
2,4*(6-3*8,5)+4,3=1,7-5,2*8,5
14,4-61,2+4,3=1,7-44,2
-42,5=-42,5
14,4-7,2х+4,3=1,7-5,2х
-7,2х+5,2х=-14,4-4,3+1,7
-2х=-17
х=17:2
х=8,5
--------------------------------------------
2,4*(6-3*8,5)+4,3=1,7-5,2*8,5
14,4-61,2+4,3=1,7-44,2
-42,5=-42,5
Похожие вопросы
Предмет: Алгебра,
автор: macykvitalik281
Предмет: Қазақ тiлi,
автор: orynbasarmaral1
Предмет: География,
автор: adikzheksenbai
Предмет: Математика,
автор: Yurok97
Предмет: Математика,
автор: koshelkovalaksa